The Effectiveness of Social Media Marketing Strategies on Purchase Intention in Skincare: A Mediating Role of Brand Image among Generation Z - Nita Mardiana Telaumbanua; Edwin Zusrony; Pemilia Sulistyowati (Pusat Riset dan Inovasi Nasional, 2026)
This research is expected to analyze the impact of social media marketing towards purchase intention with brand image as a mediating variable for users skincare product. The approach employed in this research is quantitatively with primary data collected by using a questionaire distributed to all respondents and assessment parameter with Likert scale 1-5. The research objects were generation Z, namely respondents who are 18-28 years old and have already bought skin care products at least once for the past six months through an electronic commerce application hearth that they live in Semarang Regency. The sample consisted of 80 respondents who were chosen purposively. Analysis was built on the SEM-PLS methodology implemented by SmartPLS software version 4.1.1.2 Data processing technique was SEM-PLS model. The findings of the research indicate that social media marketing has a positive and significant effect on brand image. Purchase intention is positively influenced by social media marketing. Brand image positively influences purchase intention to a great extent. Brand image Your ultimate goal is to use your external corporate identity applications in order to acquire a sustainable and positive brand image among your target audience.